KETERAMPILAN MANAGERIAL KEPALA MADRASAH TERHADAP PELAKSANAAN PERENCANAAN PEMBANGUNAN DI MI AL-FATAH ABEPANTAI - Watora, Ibrahim; Yusuf, Muhamad; Zulihi, Zulihi; Rosadi, Asep; Mayalibit, M Yasin Un; Haisang, Haisang (Waniambey: Journal of Islamic Education, 2024)
The purpose of this study was to determine the relationship between the necessity of Managerial Skills of the school principal of Madrasah on the Implementation of Development Planning at Madrasah Ibtidaiyah Al-Fatah Abepantai Jayapura City, as well as supporting and hindering factors in the Implementation of Development Planning of Al-Fatah Abepantai Madrasah Al-Fatah Jayapura City. The research method was quantitative research. An associative model leads to a causal relationship, survey method, using deductive logic starting from theory, hypothesis, observation, generalization, and accepting or rejecting the hypothesis. Using the ordinal scale -without going through the instrument validity test, using non-parametric statistics- the number of samples is 13 people using the Spearman Rank correlation. The research results are some factors that strengthen and weaken the urgency of leadership skills. While the relationship between the two variables has a significant relationship level. For an error rate of 5%, the Rho table price = 0.6318681319 > 0.591 if n = 12 and 0.6318681319 > 0.544 if n = 14. Moreover, the value of the T count is greater than the T table, then Ho is rejected, and Ha is accepted (price 2.7 > 2.160). The significant test of the correlation coefficient (whether the correlation coefficient can be generalized or not) using either table ρor using the formula both resulted in the rejection of Ho and acceptance of Ha.